Performance analysis of multi-UAV-assisted backscatter communication system - Dao Zhang; Quanyong Fu; Weinong Wu; Taotao Zhong (EURASIP Journal on Advances in Signal Processing)
Abstract The Internet of Things (IoT) technology has broad application prospects, but for the large-scale decentralized deployment of IoT devices, energy supply and data collection are the two challenges faced by IoT applications. UAV-assisted backscatter communication (BackCom) has the advantages of fast deployment, strong flexibility, and high line-of-sight (LoS) probability. Combining UAV technology with IoT applications to construct the multi-UAV-assisted BackCom system can effectively solve IoT’s energy supply and data collection problems and effectively promote the development of IoT technology. In practical applications, factors such as node distribution and UAV deployment should be considered comprehensively. This paper uses the Matérn clustering process (MCP) to model the node distribution of hotspot clustering scenarios and studies the working mechanism of using a radio frequency (RF) source carried by UAV to supply energy to a backscatter device (BD) and collecting data generated by the BD using a backscatter receiver. The approximate distribution functions of BD harvesting energy, BD activation probability, and system average coverage probability are derived. The correctness of the theoretical derivation was verified through Monte Carlo simulation, and the effects of UAVs altitude, density, and transmission power on BD activation probability and system average coverage probability were analyzed. The effectiveness of the multi-UAV-assisted BackCom system in hotspot clustering scenarios was verified.